Seasonal and decadal variability of dust observations in the Kangerlussuaq area, west Greenland - Joanna E. Bullard; Tom Mockford (Arctic, Antarctic, and Alpine Research, 2018)
Dust emissions from high-latitude, cold-climate environments have started receiving more attention in the past decade. This is because emission frequency and magnitudes are expected to increase with rising global temperatures, leading to a reduction in terrestrial ice masses and increases in suitable sediment for the aeolian system. Of the identified high-latitude dust source regions, Greenland has received relatively little attention. Using World Meteorological Organization (WMO) dust-code analysis, this study presents a seventy-year record of dust events and preferential dust transport pathways from Kangerlussuaq, west Greenland. A clear seasonal pattern of dust emissions shows increases in dust events in spring and autumn driven by effective winds and sediment supply. The decadal record suggests an increase in the magnitude, but not frequency, of dust events since the early 1990s. Pathways analysis suggests that dust is preferentially transported away from the Greenland Ice Sheet (GrIS) toward the Davis Strait and Labrador Sea. When dust is transported toward the GrIS, it is more likely to be deposited in the ice-marginal ablation zone than on the higher altitude areas of the ice sheet. The impact of dust deposition on terrestrial, cryospheric, and aquatic environments is also discussed.